Clinicopathological Study of Upper GI Malignancy in Tertiary Care Centre of Nepal - Gautam, Ajay Kumar; Dewan, Khus Raj; Patowary , Bhanumati Saikia (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Upper gastrointestinal malignancies are among the most common causes for cancer related morbidity and mortality. These cancers rapidly progress to advanced stages even in the absence of significant symptoms, thus leading to delayed diagnosis and dismal prognosis. The aim of this study was to determine the prevalence, type and clinicopathological characteristics of upper gastrointestinal tumors. Methods This was a three year cross-sectional study involving 66 patients of upper gastrointestinal cancer. The study was conducted from March 2018 to February 2021 at the college of medical sciences-Teaching Hospital, Nepal. Relevant clinical information, Endoscopic pattern and histological characterization were recorded. SPSS version 25.0 was applied for statistical analysis. Results Total 66 patients were enrolled into this study. The mean age of the population was 59.13± 13.38 years with male predominance (M:F-1.36:1). Common presenting symptoms were abdominal pain (76%), significant weight loss (61%), vomiting (40%). About 77% of the tumors were located in the stomach, 17% in the esophagus and 6% in the first and second part of the duodenum. Most common endoscopic pattern of upper gastrointestinal lesion was ulceroproliferative type (53%).Tissue histology showed adenocarcinoma as the commonest histological pattern with 82% followed by squamous cell carcinoma 10%. Conclusions These malignancies can rapidly progress to advanced stages even in the absence of serious symptoms and endoscopy is needed in suspected patients to avoid delayed diagnosis and improve the disease outcome.